TINGKAT KEPUASAN PASIEN BPJS RAWAT JALAN TERHADAP PELAYANAN PANAH RSUD GENTENG BANYUWANGI - kukuh handojo (JURNAL ILMIAH FARMASI AKADEMI FARMASI JEMBER, 2021)
The "PANAH" programme is one of the innovative Pharmacy Installation services at RSUD Genteng. PANAH is an abbreviation of Pangkas Antrian Ambil Obat Harian. This program is a new program and there has never been a measurement of the level of satisfaction so that it is necessary to measure the level of satisfaction.This study aims to determine the level of satisfaction of patients served by the “PANAH” program at RSUD Genteng based on five dimensions of service quality, namely tangible, reliability, responsiveness, empathy, assurance.The type of research used is descriptive quantitative research with cross sectional design and the sample technique used is total sampling. Samples taken were 72 patients. Technique of answering data using a questionnaire.Based on the results of the study obtained as follows. On the dimensions of physical evidence (tangible) 43 respondents were satisfied (59,72%), 29 respondents were quite satisfied (40,28%). On the credibility dimension (reliability) 45 respondents were satisfied (62,5%), 27 respondents were quite satisfied (37,5%). On the dimension of responsiveness (responsiveness) 45 respondents were satisfied (62,5%), 27 respondents were quite satisfied (37,5%). On the dimension of empathy (emphaty) 42 respondents were satisfied (58,33%), 30 respondents were quite satisfied (41,67%). On the assurance dimension 41 respondents were satisfied (56,94%), 31 respondents were quite satisfied (43,06%). In the response of fifth dimension, namely tangible, reliability, responsiveness, empathy, assurance 52 respondents were satisfied (72,22%), 20 respondents were quite satisfied (27,78%), there were no respondents who were less satisfied and dissatisfied.